من التنمية الشاملة إلي التنمية المحلية المستدامة: قراءة في المفاهيم والأبعاد والمعوقات - زبير، محمد; شبوب، محمد Shabboub, Mohamed (المركز الجامعي أحمد زبانة غليزان - مخبر الدراسات الاجتماعية والنفسية والانثروبولوجية, 2017)
Officials in both developed and developing countries are giving more importance to sustainable local development as it participates to the upgrading of the local communities through the increase of job opportunities, the rise of revenues and the amelioration of the standard of living of the individuals. As a matter of fact, various activities related to economy, culture and society as a whole may witness a positive impact. The ability of the nation to achieve a global development should be based upon its local enterprises and their capacity to create growth by giving a great credit to sustainable local development. Local decision makers are nowadays becoming more influent and have the authority to choose the right decisions which can lead to economic growth and to a better local sustainable development and then to a nationwide global development with more efficiency and competence.
لقد أصبح موضوع التنمية المحلية المستدامة يعنى باهتمام خاص من قبل مسؤولي الدول المتقدمة والنامية على حد سواء، كونه يساهم بشكل كبير في ترقية المجتمعات المحلية من خلال رفع مستوى التوظيف، والدخل، وتحسين المستوى المعيشي للأفراد، ومن ثم المساهمة بالنهوض بالاقتصاد الوطني ككل وتنميته، وذلك لما له من انعكاسات إيجابية على الجوانب الاقتصادية والاجتماعية والثقافية وغيرها. فقدرة الدولة على تحقيق التنمية الشاملة يقوم في الأساس على قدرة المؤسسات المحلية في تحقيق أهدافها الإنمائية المحلية المستدامة، كونها أصبحت في الوقت الحالي أكثر استجابة وقدرة على تحديد أولويات التنمية عن طريق صناع القرار المحليين الذين هم أكثر الماما بالشؤون المحلية، وهذا ما يساهم في تحقيق أهداف التنمية المحلية المستدامة ومن ثم الوطنية الشاملة بأكثر كفاءة فعالية.
Keywords: سوسيولوجيا التنمية -- الاقتصاد البيئي -- جودة الحياة